7-Chloro-4-[(E)-2-(2-methoxybenzylidene)hydrazin-1-yl]quinoline monohydrate - de Souza, Marcus V. N. (International Union of Crystallography, 2010)
In the title hydrate, C(17)H(14)ClN(3)O·H(2)O, the dihedral angle between the quinoline fused-ring system and the benzene ring is 13.4 (2)° and the conformation about the C=N bond is E. In the crystal, N(h)—H⋯O(w) and O(w)—H⋯N(q) (h = hydrozone, w = water and q = quinoline) hydrogen bonds generate a two-dimenstional network in the ac plane. A weak C—H⋯O interaction helps to consolidate the packing.